Sports Results and the Profitability of Sponsorship Companies on the Example of Volleyball Clubs - Szymański, Marek; Wojtalik, Grzegorz (Journal of Finance and Financial Law, 2021)
The purpose of the article is to investigate the relationship between the sports performance of volleyball teams in Poland and the rates of return of the titular sponsors, whose shares are listed on the Warsaw Stock Exchange. The four most successful Polish PlusLiga volleyball teams in the 21st century were selected for this study.Methodology: The article describes the results carried out using ARCH and GARCH models.Results of the research: Two groups of results were obtained. For two companies – JSW and ASSECO – the sports results of volleyball teams and betting forecasts for their matches had a statistically significant impact on the stock performance of these companies. For two companies – PGE and Azoty – no such relationship has been found. Moreover, all of the stock returns were significantly influenced by the WIG index. On the other hand, neither of the companies were influenced by the match day.